Thermospheric Composition O/N 2 Response to an Altered Meridional Mean Circulation During Sudden Stratospheric Warmings Observed by GOLD. Issue 1 (6th January 2020) - Oberheide, J.; Pedatella, N. M.; Gan, Q.; Kumari, K.; Burns, A. G.; Eastes, R. W.
Abstract: Observations from the recently launched Global‐Scale Observations of the Limb and Disk (GOLD) instrument on the geostationary SES‐14 communications satellite reveal a substantial response of the mean state of the thermosphere to the Sudden Stratospheric Warming (SSW) event in early January 2019. The observed O/N 2 column density depletion of more than 10% starts at the onset of the SSW, maximizes at the time of the stratospheric wind reversal, and recovers toward the end of the SSW. A connection between SSW and thermospheric composition was previously predicted by model simulations but could not be observed before. The GOLD measurements support the scenario that enhanced global‐scale wave activity during SSWs causes an enhanced wave driving of the lower thermosphere zonal mean circulation that leads to a reduction in lower thermosphere atomic oxygen, which then propagates through molecular diffusion into the upper thermosphere. Plain Language Summary: Global‐Scale Observations of the Limb and Disk measurements provide the first observational proof of model predictions that the breakup of the stratospheric polar vortex changes the composition of the thermosphere. The important O/N 2 ratio is depleted by ∼ 10% through a rather complex chain of processes that connect global‐scale waves from the lower atmosphere, wave dissipation, mean meridional circulation, turbulent eddy transport, and molecular diffusion to produce a global O/N 2 reduction in the thermosphere. The observed composition changes will likely impact Earth's ionospheric plasma environment and imply a substantial impact of the lower and middle atmosphere on space weather. Key Points: A global O/N 2 column density depletion is observed by GOLD between late December 2018 and early January 2019 Depletion is driven by zonal mean circulation changes due to enhanced wave driving during SSW GOLD provides observational proof that the weather of the polar stratosphere changes the mean state of the thermosphere